Making Synapses Strong: Metaplasticity Prolongs Associativity of Long-Term Memory by Switching Synaptic Tag Mechanisms. (9th October 2012) - Li, Qin; Rothkegel, Martin; Xiao, Zhi Cheng; Abraham, Wickliffe C; Korte, Martin; Sajikumar, Sreedharan
Abstract : One conceptual mechanism for the induction of associative long-term memory is that a synaptic tag, set by a weak event, can capture plasticity-related proteins from a nearby strong input, thus enabling associativity between the 2 (synaptic tagging and capture, STC). So far, STC has been observed for only a limited time of 60 min. Nevertheless, association of weak memory forms can occur beyond this period and its mechanism is not well understood. Here we report that metaplasticity induced by ryanodine receptor activation or synaptic activation of metabotropic glutamate receptors prolongs the durability of the synaptic tag, thus extending the time window for associative interactions mediating storage of long-term memory. We provide evidence that such metaplasticity alters the mechanisms of STC from a CaMKII-mediated (in non-primed STC) to a protein kinase Mzeta (PKMζ)-mediated process (in primed STC). Thus the association of weak synapses with strong synapses in the "late" stage of associative memory formation occurs only through metaplasticity. The results also reveal that the short-lived, CaMKII-mediated tag may contribute to a mechanism for a fragile form of memory while metaplasticity enables a PKMζ-mediated synaptic tag capable of prolonged interactions that induce a more stable form of memory that is resistant to reversal.